2010
DOI: 10.1126/science.1187300
|View full text |Cite
|
Sign up to set email alerts
|

Fairness and the Development of Inequality Acceptance

Abstract: Fairness considerations fundamentally affect human behavior, but our understanding of the nature and development of people's fairness preferences is limited. The dictator game has been the standard experimental design for studying fairness preferences, but it only captures a situation where there is broad agreement that fairness requires equal split. In real life, people often disagree on what is fair, largely because they disagree on whether individual achievements, luck, and efficiency considerations of what… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

35
284
0
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 360 publications
(322 citation statements)
references
References 29 publications
35
284
0
3
Order By: Relevance
“…However, social preferences is a broad term and little progress has been made so far in identifying and classifying different kinds of social preferences among children and adolescents. A recent exception is Almås et al (2010), who study 486 subjects aged 10 to 19 and find that while the youngest children are mostly egalitarian and the older ones are more efficiency oriented, there is no change in selfishness from mid-childhood to late adolescence. In the present paper, we explore differences in social preferences among three different age groups using the experimental design and classification of preferences according to Charness and Rabin (2002).…”
Section: Introductionmentioning
confidence: 99%
“…However, social preferences is a broad term and little progress has been made so far in identifying and classifying different kinds of social preferences among children and adolescents. A recent exception is Almås et al (2010), who study 486 subjects aged 10 to 19 and find that while the youngest children are mostly egalitarian and the older ones are more efficiency oriented, there is no change in selfishness from mid-childhood to late adolescence. In the present paper, we explore differences in social preferences among three different age groups using the experimental design and classification of preferences according to Charness and Rabin (2002).…”
Section: Introductionmentioning
confidence: 99%
“…Our study contributes to the literature on what people view as a fair distribution and how fairness considerations shape individual behavior (e.g., Fehr and Schmidt, 1999;Konow, 2000;Cherry, Frykblom, and Shogren, 2002;Falk, Fehr, and Fischbacher, 2003;Tyran and Sausgruber, 2006;Cappelen, Drange Hole, Sørensen, and Tungodden, 2007;Konow, Saijo, and Akai, 2009;Almås, Cappelen, Sørensen, and Tungodden, 2010;Cabrales, Miniaci, Piovesan, and Ponti, 2010;Rodriguez-Lara and Moreno-Garrido, 2012;Cappelen, Moene, Sørensen, and Tungodden, 2013b;Durante, Putterman, and Weele, 2014;Bartling, Weber, and Yao, 2015;Jakiela, 2015). A number of papers both in social psychology and in behavioral economics have shown that a majority of people appear to view income inequalities as fair if the inequalities are proportional to differences in performance (e.g., Adams, 1965;Walster, Berscheid, and Walster, 1973;Leventhal, 1980;Konow, 2000;Frohlich, Oppenheimer, and Kurki, 2004;Cappelen, Sørensen, and Tungodden, 2010;Cappelen et al, 2007Cappelen et al, , 2013a.…”
Section: Introductionmentioning
confidence: 74%
“…However, in the field of justice attitude research, such criticism is much more problematic. There are theoretical reasons to believe Vanberg, 2007), and there is empirical evidence that indicates (Almås et al, 2010;Keller et al, 2013;Meulemann & Birkelbach, 2001), that attitudes toward justice are not personality traits that remain stable and persistent through an individual's life course. Thus, attitudes toward justice, and judgments of what is just, are "position effects" (Boudon, 1990) in that they reflect not only the specific interests but also the experiences individuals "accumulate" in different occupational and social positions over the life course .…”
Section: Experience-based Attitudes: Attitudes Toward Justice and Thementioning
confidence: 99%